Assessment of Fire and Life Safety in Rural Settlements in India - Kuldeep Kumar; Luvditya Khurana; Meghna Raj (International Journal of Rural and Regional Development, 2024)
Fire incidents pose a significant threat to life and property in rural India, particularly in residences. Despite strides in urban fire safety, rural areas continue to face frequent fire incidents, posing significant risks to lives and properties. This paper presents a thorough review of existing literature on fire safety assessment in rural Indian settlements focusing on unique vulnerabilities specific to this context. In rural settings, various factors contribute to the increased risk of fire outbreaks, including the prevalent use of traditional building materials, unregulated cooking practices, inadequate electrical infrastructure, unsafe storage practices, and human behavior patterns. Understanding these factors is crucial for developing effective fire prevention strategies tailored to rural environments. By identifying primary fire causes, stakeholders can explore relevant prevention measures and interventions to enhance safety in rural settlements. This paper aims to fill the gap in the literature by examining the multifaceted nature of fire safety in rural India and proposing actionable insights for stakeholders. It emphasizes the importance of community involvement, innovative strategies, and policy implications in addressing fire safety challenges. By fostering collaboration among government agencies, local communities, and non-governmental organizations, sustainable solutions can be developed to mitigate the risks associated with fire incidents in rural areas. This study also underscores the critical need for tailored approaches to rural fire safety and promotes enhanced safety standards in building design, infrastructure development, and public awareness campaigns. By incorporating local knowledge, cultural practices, and community participation into fire safety initiatives, stakeholders can effectively address the unique challenges faced by rural settlements in India, ultimately saving lives and protecting property.
Keywords: fire risk; fire safety; life safety; rural settlement